From lab to industry: Analysing the performance of ceramic batch modified with sodium silicate and phosphoric acid-based additive in ceramic floor tile production - Zoran Bačkalić; Milica V. Vasić; Berta Barta Holló; Djordje Jovanović; Siniša Sremac; Paul Awoyera (Next Materials, 2025)
This study investigates the use of CERADIT+ , a mixed phosphate-sodium silicate additive, to enhance porcelain stoneware ceramic tile properties during a 50-minute cold-cold firing cycle. Used in amounts up to 0.50 %, CERADIT+ acted as a firing binder, with optimal mechanical properties observed at 0.25 % in lab tests. Scale-up trials maintained consistent raw materials and processing steps, including wet milling, spray drying, pressing, and firing, with compaction pressures between 300–330 kg/cm² and thicknesses of 7.0–8.1 mm. Instrumental analysis tracked mineralogical changes and gas evolution during firing. All the laboratory and industrial probes with CERADIT+ met standard floor tile specifications. However, the modulus of rupture and water absorption varied among the industrially-fired tiles, indicating a possible agglomeration of the additive-derived phases during firing. Notably, a low quantity of berlinite agglomerated in the additive-enhanced tiles. This mineralogical shift suggests a distinct reaction pathway introduced by the additive. Furthermore, introducing sodium silicate in a low amount promoted better densification of the fired pieces. The findings support CERADIT+ as a viable additive for industrial ceramic tile production, and future research will explore its optimization across different ceramic bodies. Using this additive is expected to achieve up to 30 % savings in natural gas consumption and a corresponding reduction of up to 30 % in CO₂ emissions.